The Relationship Between Corporate Governance and Reputation on Financial Markets: Evidence From Turkey - GÜNDOĞDU, Aysel (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<span style="font-size: 12pt; line-height: 115%; font-family: ’Times New Roman’, serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-US">This study aims to measure the relation between corporate governance and reputation management, which has been gradually important for banks. Reputation fact, which may be perceived differently in every sector and business, has a distinctive structure in finance sector, too. Banks, having direct relationship with money, totally take on a reputation job. However, conducted international and national studies show that financial institutions and especially banks take place in sub steps within all sectors in reliance grading. This situation forms a paradox in itself and the fact that institutions, whose job is reputation, are the institutions, having lowest reputation, leads to discussion. In this study, the relationship between reputation management and corporate governance of İşbank and Turkcell